Land, water, and agriculture in Egypt: the economywide impact of policy reform - Robinson, Sherman; Gehlhar, Clemen G. (International Food Policy Research Institute, 1995)
The tax and subsidy system in Egypt in 1986-88 was very distorted, involving large, sectorally variegated, ouput taxes and subsidies. In agriculture, there were also major input subsidies and no charges for water. In this paper, an 11-sector, computable general equilibrium (CGE) model is used to capture this mix of policies, focusing on land and water use in agriculture and on the links between agriculture and the rest of the economy.